2009
DOI: 10.1111/j.1872-034x.2009.00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Source of transmission in children with chronic hepatitis B infection after the implementation of a strategy for prevention in those at high risk

Abstract: Although vaccine failure of mother-to-child transmission was the major cause of chronic HBV infection in children, father-to-child transmission was the second most common mode of transmission. In addition, sibling-to-sibling transmission was found. Unless at-risk individuals and groups can be accurately identified to prevent horizontal transmission, the introduction of universal vaccination is essential for achieving the elimination of HBV infection in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Results from previous studies (7,9,24) have suggested that neonatal populations with a HBsAg-positive father have a higher prevalence of HBV infection; thus, they are a high risk population of HBV infection. However, the rate of transmission has differed among the various studies, and no consistent conclusions have been drawn (25,26) One reason may be that the diagnostic criteria used by the institutes were not uniform.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results from previous studies (7,9,24) have suggested that neonatal populations with a HBsAg-positive father have a higher prevalence of HBV infection; thus, they are a high risk population of HBV infection. However, the rate of transmission has differed among the various studies, and no consistent conclusions have been drawn (25,26) One reason may be that the diagnostic criteria used by the institutes were not uniform.…”
Section: Discussionmentioning
confidence: 98%
“…However, vertical transmission occurs through germ cells. In particular, fathers positive for HBsAg, hepatitis B e antigen (HBeAg) and hepatitis B core antigen (anti-HBc) are more likely to transmit the infection to the infant via vertical transmission; father-to-child transmission is the second most important pathway of HBV vertical transmission (9). Methods of blocking father-to-infant vertical transmission remain limited in the medical field; thus, further research is required.…”
Section: Introductionmentioning
confidence: 99%
“…The research of Huang et al (2003) suggested that infection by HBV could cause chromosomal mutation in patient sperm, and that integration of HBV DNA into sperm chromosomes is a random and multi-locus event, increasing the instability of sperm chromosomes and causing widespread influence lasting for generations. Other studies (Ali et al, 2005;Takegoshi and Zhang, 2006;Komatsu et al, 2009) indicated that infants with HBsAg (+) fathers were the highest risk group for vertical transmission. However, the reported transfection rates were variable (Wang et al, 2003b;Cai and Zhu, 2013), probably because of different diagnostic criteria applied and different populations selected across studies.…”
Section: Hbv Vertical Transmission From Father To Infant and Its Tranmentioning
confidence: 99%
“…When HBV is passed on to the child through the father's sperm, it is defined as vertical transmission. Vertical transmission from father to child is more likely to occur when the father is HBsAg-, HBeAg-, and HBcAb-positive, and it has become the second most important mechanism of vertical transmission (just below mother-to-child vertical transmission) (Komatsu et al, 2009). The research of Huang et al (2003) suggested that infection by HBV could cause chromosomal mutation in patient sperm, and that integration of HBV DNA into sperm chromosomes is a random and multi-locus event, increasing the instability of sperm chromosomes and causing widespread influence lasting for generations.…”
Section: Hbv Vertical Transmission From Father To Infant and Its Tranmentioning
confidence: 99%
“…Vertical transmission is the second most important method of spreading HBV (15), particularly in fathers who are HBsAg-, HBeAg-and anti-HBc-positive. The presence of HBsAb in females prior to pregnancy is widely accepted to play a positive role in blocking vertical transmission from father to infant; however, in married couples with an HBsAg-positive father, it is common for pregnancy-associated testing to identify no HBsAb, for Table IV.…”
Section: P-value T-value --------------------------------------------mentioning
confidence: 99%